2017
DOI: 10.1007/s40272-017-0224-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability and Efficacy of Drugs for Treating Behavioural Insomnia in Children with Attention-Deficit/Hyperactivity Disorder: A Systematic Review with Methodological Quality Assessment

Abstract: ObjectiveA large proportion of paediatric patients with attention-deficit/hyperactivity disorder (ADHD) have associated sleep problems which not only affect the child's well-being but also impact family functioning. Management of sleep problems is consequently an important aspect of overall ADHD management in paediatric patients. Although some drugs are being used off-label for the management of paediatric insomnia, there is scant clinical evidence supporting their use. Our aim was to identify and assess the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 65 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…Proof of the efficacy of melatonin in sleep latency and sleep duration in ADHD children has been supported by observational studies 16. Mohammadi et al17 explored the efficacy of melatonin in children with ADHD receiving MPH in a placebo-controlled study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof of the efficacy of melatonin in sleep latency and sleep duration in ADHD children has been supported by observational studies 16. Mohammadi et al17 explored the efficacy of melatonin in children with ADHD receiving MPH in a placebo-controlled study.…”
Section: Introductionmentioning
confidence: 99%
“…Proof of the efficacy of melatonin in sleep latency and sleep duration in ADHD children has been supported by observational studies. 16 Mohammadi et al 17 explored the efficacy of melatonin in children with ADHD receiving MPH in a placebo-controlled study. This study reported a positive effect of melatonin (3–6 mg/d) on sleep latency and overall sleep disturbances, without effects on ADHD measures.…”
Section: Introductionmentioning
confidence: 99%
“…Seven systematic reviews reported about the efficacy of medication on ADHD symptoms in patients with comorbid disorders [149][150][151][152][153][154][155][156]. For example, both MPH and ATX were efficacious in reducing ADHD symptoms also in youth with ASD [149].…”
Section: Efficacy Of Medication On Adhd Symptoms In Patients With Com...mentioning
confidence: 99%
“…This is particu-larly an alarming given that the FDA (Food and Drug Administration) has not yet approved any medication for treatment of insomnia in children, even if many drugs are currently prescribed off-label for insomnia in children. [59][60][61] While prescription medication has not been approved, evidence form published studies in the past 15 years supports the overall efficacy and tolerability of melatonin for insomnia in children. [62][63][64][65][66] Melatonin is considered particularly beneficial for insomnia in children with autism 67,68 or special needs.…”
Section: Treatmentmentioning
confidence: 99%